A companion to the anthropology of death - Robben, Antonius C. G. M. (Blackwell companions to anthropology, 2018)
Prominent scholars present their most recent work about mortuary rituals, grief and mourning, genocide, cyclical processes of life and death, biomedical developments, and the materiality of human corpses in this unique and illuminating book. Interrogating our most common practices surrounding death, the authors ask such questions as: How does the state wrest away control over the dead from bereaved relatives? Why do many mourners refuse to cut their emotional ties to the dead and nurture lasting bonds? Is death a final condition or can human remains acquire agency? The book is a refreshing reassessment of these issues and practices, a source of theoretical inspiration in the study of death.